Uptake and translocation mechanisms of different forms of organic selenium in rice (Oryza sativa L.) - Wang, Qi; Kong, Lingxuan; Huang, Qingqing; Li, Huafen; Wan, Yanan (Frontiers in Plant Science, 2022)
Selenium is an essential trace element for human and animal health, and toward an understanding of the uptake and translocation of Se in plants is important from the perspective of Se biofortification. In this study, we conducted hydroponic experiments to investigate the mechanisms of organic Se [selenomethionine (SeMet) and selenomethionine-oxide (SeOMet)] uptake, translocation, and the interactions between SeMet and SeOMet in rice. We also investigated differences in the dynamics of organic and inorganic Se uptake by rice roots. Concentration-dependent kinetic results revealed that SeMet uptake during a 1 h exposure was 3.19–16.0 times higher than that of three other Se chemical forms, with uptake capacity (Vmax) values ordered as follows: SeMet>SeOMet>selenite>selenate. Furthermore, time-dependent kinetic analysis revealed that SeMet uptake by roots and content in shoots were initially clearly higher than those of SeOMet, although the differences gradually diminished with prolonged exposure time; while no significant difference was found in the transfer factor of Se from rice roots to shoots between SeMet and SeOMet. Root uptake of SeOMet was significantly inhibited by carbonyl cyanide 3-chlorophenylhydrazone (CCCP) (30.4%), AgNO3 (41.8%), and tetraethylammonium chloride (TEACl) (45.6%), indicating that SeOMet uptake is a metabolically active process, and that it could be mediated via aquaporins and K+ channels. Contrarily, SeMet uptake was insensitive to CCCP, although markedly inhibited by AgNO3 (93.1%), indicating that rice absorbs SeMet primarily via aquaporins. Furthermore, Se uptake and translocation in rice treated simultaneously with both SeMet and SeOMet were considerably lower than those in rice treated with SeMet treatment alone and notably lower than the theoretical quantity, indicating interactions between SeMet and SeOMet. Our findings provide important insights into the mechanisms underlying the uptake and translocation of organic Se within plants.